Aller chez le notaire : un moyen d’expression pour les femmes ? L’exemple de Tours au XVIIIe siècle - Célia Drouault (Genre & Histoire)
This article explores the position of women in early modern Tours through the examination of women’s notarial practices. Notary offices were places where women could express themselves, albeit within the relatively narrow framework of the law. Not only did they perform their legal duties, but they often stood up for their rights. Women’s involvement was far from marginal, since single and married women as well as widows accounted for almost half of the notaries’ customers. Notarial practice at times represented a moment of freedom for women as some legal documents enabled even married women to appear on their own. But this freedom was most apparent during auctions. For practical reasons during these sales auctioneers took liberties with the law, which benefitted women; this highlights the gap that could exist between law and its practice.